2016
DOI: 10.1186/s12889-016-3734-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the mortality risks of nursing professionals with diabetes and general patients with diabetes: a nationwide matched cohort study

Abstract: BackgroundNursing professionals have received comprehensive medical education and training. However, whether these medical professionals exhibit positive patient care attitudes and behaviors and thus reduce mortality risks when they themselves are diagnosed with chronic diseases is worth exploring. This study compared the mortality risks of female nurses and general patients with diabetes and elucidated factors that caused this difference.MethodsA total of 510,058 female patients newly diagnosed with diabetes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…As far as we know, this is the first study to give a comprehensive overview of the prognosis of people with type 2 diabetes across occupational groups. However, a Chinese study found lower death rates in nurses with diabetes than the general population of patients [ 26 ], which is in line with our findings. Previous studies indicate that low SES is associated with higher rates of mortality and CVD in individuals with type 2 diabetes [ 9 , 10 ].…”
Section: Discussionsupporting
confidence: 92%
“…As far as we know, this is the first study to give a comprehensive overview of the prognosis of people with type 2 diabetes across occupational groups. However, a Chinese study found lower death rates in nurses with diabetes than the general population of patients [ 26 ], which is in line with our findings. Previous studies indicate that low SES is associated with higher rates of mortality and CVD in individuals with type 2 diabetes [ 9 , 10 ].…”
Section: Discussionsupporting
confidence: 92%
“…To what extent this is reflected in high morbidity and sickness absence and disability pension is not known. Recent Swedish studies indicate that low SES is associated with increased risk of diabetes complications [24] and disability related to diabetes [25], but few studies have explored the risk of comorbidity and work disability across different occupational groups [26]. It seems possible that workplace factors such as irregular working hours, shift work, stress and physically strenuous work may hinder optimal self-management and contribute to excess risk of complications.…”
Section: Discussionmentioning
confidence: 99%
“…Although the older nurse subgroups had lower risks of both stroke types than their counterparts, the risks still increased with aging. This could be because the nurses receive medical education and training, and thus have knowledge regarding the prevention of chronic diseases [15,16]; they can apply such knowledge to adjust their lifestyles in order to prevent diseases and reduce the death rate from such diseases. Furthermore, studies have reported consistent results that the risk of chronic diseases was lower in health care professionals [15,16,17,18,19].…”
Section: Discussionmentioning
confidence: 99%
“…(1) Nurses receive medical education and have a higher rate of health-seeking behavior when they discover any anomalies in their bodies. They also commonly maintain healthy lifestyles, thereby promoting personal well-being and lowering the risk of stroke [15,16,17,21]. (2) Nurses also enjoy convenient access to medical care in the event of disease incidence [22,23,24].…”
Section: Discussionmentioning
confidence: 99%